Interventions for Adolescent Mental Health: An Overview of Systematic Reviews - Das, Jai K.; Salam, Rehana A.; Lassi, Zohra S.; Khan, Marium Naveed; Mahmood, Wajeeha; Patel, Vikram; Bhutta, Zulfiqar A. (Journal of adolescent health, 2016)
Many mental health disorders emerge in late childhood and early adolescence and contribute to the burden of these disorders among young people and later in life. We systematically reviewed literature published up to December 2015 to identify systematic reviews on mental health interventions in adolescent population. A total of 38 systematic reviews were included. We classified the included reviews into the following categories for reporting the findings: school-based interventions (n = 12); community-based interventions (n = 6); digital platforms (n = 8); and individual-/family-based interventions (n = 12). Evidence from school-based interventions suggests that targeted group-based interventions and cognitive behavioral therapy are effective in reducing depressive symptoms (standard mean difference [SMD]: −.16; 95% confidence interval [CI]: −.26 to −.05) and anxiety (SMD: −.33; 95% CI: −.59 to −.06). School-based suicide prevention programs suggest that classroom-based didactic and experiential programs increase short-term knowledge of suicide (SMD: 1.51; 95% CI: .57–2.45) and knowledge of suicide prevention (SMD: .72; 95% CI: .36–1.07) with no evidence of an effect on suicide-related attitudes or behaviors. Community-based creative activities have some positive effect on behavioral changes, self-confidence, self-esteem, levels of knowledge, and physical activity. Evidence from digital platforms supports Internet-based prevention and treatment programs for anxiety and depression; however, more extensive and rigorous research is warranted to further establish the conditions. Among individual- and family-based interventions, interventions focusing on eating attitudes and behaviors show no impact on body mass index (SMD: −.10; 95% CI: −.45 to .25); Eating Attitude Test (SMD: .01; 95% CI: −.13 to .15); and bulimia (SMD: −.03; 95% CI: −.16 to .10). Exercise is found to be effective in improving self-esteem (SMD: .49; 95% CI: .16–.81) and reducing depression score (SMD: −.66; 95% CI: −1.25 to −.08) with no impact on anxiety scores. Cognitive behavioral therapy compared to waitlist is effective in reducing remission (odds ratio: 7.85; 95% CI: 5.31–11.6). Psychological therapy when compared to antidepressants have comparable effect on remission, dropouts, and depression symptoms. The studies evaluating mental health interventions among adolescents were reported to be very heterogeneous, statistically, in their populations, interventions, and outcomes; hence, meta-analysis could not be conducted in most of the included reviews. Future trials should also focus on standardized interventions and outcomes for synthesizing the exiting body of knowledge. There is a need to report differential effects for gender, age groups, socioeconomic status, and geographic settings since the impact of mental health interventions might vary according to various contextual factors.